Knowledge and perception in adopting principle 5-7 of MSPO among independent smallholder case of Alor Gajah, Melaka / Ahmad Zulhilmi Hairussalleh - Hairussalleh, Ahmad Zulhilmi (Faculty of Plantation and Agrotechnology, 2019)
Oil palm is the most important crop in Malaysia. This production of oil palm contributes to 6.4% of its gross national income and is important to aspect of socio economic growth. This due to the high yield,cheap, and versatile in various applications. However ,this industry are having big issues regarding to environmental criticisim from green consumerism, pressure groups and sustainability concern from importing countries. As a result, assessment has to been constructed to identify sustainability performance of oil palm production. Malaysian Sustanainable Palm Oil implementation (MSPO) was difficult to been adapted by producer especially smallholder because of its voluntary schemes. In this study, researcher was decided to study about smallholders’ knowledge and perception wether they can adapt towards implementation of MSPO based on principle 5 until 7. This study will be held in Alor Gajah, Melaka. The population size of this study is about 100 smallholders. For this study, the researcher needs only 80 samples to analysed based on Krejcie and Morgan table. The questionnaires will be use to collect data and the questionnaires will be distributed to the selected smallholders. Pearson correlation is use to analyzed the relationship between independent and dependent variables which independent refer to knowledges and perceptions while the dependent variables is referring to principle 5-7 of MSPO. Finding of this study had shown that there is a significant and non-significant relationship between the two variables that stated earlier.